Information security policies, procedures, and standards a practitioner's reference - Landoll, Douglas J. (CRC Press, Taylor & Francis Group, 2016)
Information Security Policies, Procedures, and Standards: A Practitioner's Reference gives you a blueprint on how to develop effective information security policies and procedures. It uses standards such as NIST 800-53, ISO 27001, and COBIT, and regulations such as HIPAA and PCI DSS as the foundation for the content. Highlighting key terminology, policy development concepts and methods, and suggested document structures, it includes examples, checklists, sample policies and procedures, guidelines, and a synopsis of the applicable standards.